Applying the STEAM Approach in IPAS Learning to Instill Discipline Character in Islamic Elementary School - Fadhil Nur Hidayat; Galuh Mentari Putri (Mauve Journal De Leardu, 2026)
This research aims to describe the implementation of the STEAM approach in Natural and Social Sciences (IPAS) learning and analyze the instilling of discipline character in 4th-grade students at SD Islami Qur’ani, East Lampung. The study employed a qualitative approach with a case study design involving 12 students and one classroom teacher as research subjects. Data were collected through participant observation across six sessions, in-depth interviews, and documentation, focusing on a simple water filter project themed around the water cycle. The findings indicate that the STEAM approach effectively instills three forms of discipline character simultaneously: procedural discipline, reflected in adherence to scientific step sequences; time discipline, through the timely completion of tasks aided by timers and learning contracts; and responsibility discipline, which arises from the awareness of fulfilling roles following technical failures within the group. The internalisation of these characters was supported by the teacher's role as a facilitator, the accessibility of low-cost practical materials, and the reinforcement of Islamic values regarding amanah (trustworthiness), while inhibiting factors included variations in students' learning paces and limited meeting time. This study concludes that the natural consequences mechanism within STEAM is capable of intrinsically re-engineering student discipline through direct experience. As a recommendation, future researchers are expected to conduct longitudinal studies to test the stability and resilience of students' discipline character over a longer period and across different subject contexts.